2013
DOI: 10.1063/1.4847676
|View full text |Cite
|
Sign up to set email alerts
|

Large enhancement of Förster resonance energy transfer on graphene platforms

Abstract: In the view of the applications of Förster resonant energy transfer (FRET) in biological systems which especially require FRET in the inrared region we investigate the great advantage of graphene plasmonics in such studies. Focusing on the fundamental aspects of FRET between a donor-acceptor pair on a graphene platform showing that FRET mediated by the plasmons in graphene is broadband and enhanced by six orders of magnitude. We briefly discuss the impact of phonon-polaritonic substrates.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 34 publications
1
47
0
Order By: Relevance
“…More recently such systems have been revisited for their remarkable quantum features like squeezing [10]. Further it was shown that the energy transfer across plasmonic metal films can be enhanced [16] and that the long range plasmons allow for long-range plasmon assisted energy transfer between atoms placed on plasmonic structures such as graphene [17][18][19] and metals [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…More recently such systems have been revisited for their remarkable quantum features like squeezing [10]. Further it was shown that the energy transfer across plasmonic metal films can be enhanced [16] and that the long range plasmons allow for long-range plasmon assisted energy transfer between atoms placed on plasmonic structures such as graphene [17][18][19] and metals [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…For extended graphene nanostructures interacting with quantum emitters (QEs), e.g., graphene monolayers and graphene ribbons, the large field enhancements may be attributed to the strong confinement of the propagating surface plasmons, leading to much larger field values than in free space [20,38,39]. Large field enhancement values are also observed when the interaction between QEs and graphene disks is considered, due to the excitation of localized plasmon modes.…”
Section: Introductionmentioning
confidence: 81%
“…Problems such as the calculation of the Purcell factor and Förster energy transfer are two examples [42,43] well-suited for the Green's function approach. Here we consider another problem that also depends on the density of electromagnetic modes, the calculation of the effective polarizability of a quantum emitter.…”
Section: Renormalization Of the Polarizability Of A Quantum Emitter Nmentioning
confidence: 99%